Au doping of CdS polycrystalline films prepared by co-sputtering of CdS–Cd-Au targets (Superficies y Vacío, 2012)
Au doped CdS polycrystalline films were grown on Corning glass substrates at room temperature by co-sputtering from a CdS–Cd–Au target. Elemental Cd and Au were placed onto the CdS target covering small areas. The electrical, structural, and optical properties were analyzed as a function of Au content. The Au doped CdS polycrystalline films showed a p-type semiconductor nature. It was found that the electrical resistivity drops and the carrier concentration increases as a consequence of Au incorporation within the CdS lattice. In both cases, the changes were of several orders of magnitude.